Biochip array technology for new psychoactive substances detection in biological samples: Evaluation of the specificity of the Randox Evidence Investigator®. (September 2022) - Deville, Marine; Bailly, Ronald; Gauthier, Nicolas; Pitti, Pauline; Wachtelaer, Audrey; Charlier, Corinne
Background: The need to detect new psychoactive substances in biological samples is of crucial interest. In this paper, the specificity of a benchtop immunoanalyzer commercialized by Randox was evaluated on real patient samples. Method: The Evidence Investigator was assessed to screen for NPS on 80 serum and urine samples coming from patients admitted to the emergency department. Targeted NPS were included in various categories such as synthetic cannabinoids, opioids and benzodiazepines. Results were compared with a chromatographic technique coupled with mass spectrometry. Results: No NPS was detected by the reference technique. Concerning immunoanalysis, some piperazines were positive, caused by the presence of medicine containing this chemical structure. Clonazepam and fentanyl derivatives were confirmed in some cases, but sometimes the positivity was explained by other opiates or benzodiazepines, which also explained two samples falsely positive for etizolam. Conclusions: The Randox Evidence Investigator was rapid and easy to use. It can be used as a first intention but always followed by a more specific technique in order to detect false positive result.